Clinical, Biochemical and Molecular Characteristics of Fifteen Patients with Mucopolysaccharidosis Type II in Western Turkey - Havva Yazıcı; Ebru Canda; Esra Er; Sema Kalkan Uçar; Hüseyin Onay; Ferda Özkınay; Mahmut Çoker (Galenos Yayinevi, 2018)
Aim:Mucopolysaccharidosis Type II (MPS II, Hunter syndrome, OMIM 309900) is a rare X-linked lysosomal storage disease due to a deficiency of the iduronate-2-sulfatase (IDS) enzyme, which is one of the degradative enzymes of mucopolysaccharides. The purpose of this study is to present the clinical, biochemical and molecular characteristics of fifteen patients with MPS II in western Turkey.Materials and Methods:A retrospective study was carried out on fifteen patients with MPS II who were followed up by Ege University Faculty of Medicine, Unit of Pediatric Metabolic Diseases and Nutrition between October 2004 and September 2017.Results:The age range of the patients enrolled in the study was between 11 months and 318 months at the time of diagnosis. The most common symptom was coarse face. On physical examination, all of the patients presented with coarse face, macrocephaly and organomegaly. Except for one patient, all other were severe phenotype. IDS activity was significantly decreased in all patients in whom enzyme analysis was performed. In this study, one novel mutation was described.Conclusion:This is the first study on the clinical and molecular characterization of Turkish MPS II patients. The majority of the patients had neurologic involvement with different degrees of severity. The molecular analysis revealed one novel mutation.